Sciatica - radiating pain affecting an increasing part of society - Kontowicz, Marlena; Husejko, Jakub Piotr; Porada, Mateusz; Karło, Aneta; Bursiewicz, Wiktor; Lange, Hubert; Zwolinski, Adrian; Nawrocka, Agnieszka; Łabędź, Magdalena; Romaniuk, Maciej; et al. (Journal of Education, Health and Sport, 2019)
Introduction: Sciatica is a current and more common problem affecting normal functioning. Along with the development of civilization, the lifestyle has also changed, contributing to spend a large amount of time in a sitting position. Material and Methods: Review of literature data available in the Pubmed, Cochrane and Google Scholar databases. Results: Both in a standing and sitting position, the pressure exerted on the intervertebral discs increases leading to a hernia which, pressing on the roots of the L4-S1 nerves, lead to symptoms characterized by pain in the lumbar region, back of the buttock, thigh, calf, foot and paresthesia of these areas. Due to the progressive changes associated with aging, the frequency of sciatica increases with age. The basis for the diagnosis of sciatica is a carefully collected interview and examination of the patient, while imaging and neurophysiological tests can be helpful in determining the degree of compression on nerve structures. Treatment of sciatica is dependent on the cause and can be both conservative and surgical. Conclusions: Due to the increasing number of cases of sciatica, it seems necessary to expand the knowledge on the diagnostic and therapeutic possibilities of this disease.